Penerapan Augmented Reality Sebagai Media Pembelajaran Budaya Rumah Adat Sulawesi Selatan - Victorianto Aditya Johan; Adi Chandra Syarif (TEMATIKA: Jurnal Penelitian Teknik Informatika dan Sistem Informasi, 2015)
Today, Indonesian people are not interested in learning and abandon their own culture. This is because Indonesian people have been influenced with technology and culture from another country. A cultural reading of Indonesian people are also still very low. This research designed to make application for learning about culture, especially traditional house South Sulawesi by implement Augmented Reality on a book as one of technology to help Indonesian people in studying the culture of traditional house South Sulawesi. An interactive display allows Indonesian people to interested in studying and obtain information with this application. The result of this research is the application for learning about culture traditional house South Sulawesi and book as one of the forms of learning media. With this research, Indonesian people can be helped to obtain information and learn culture of traditional house South Sulawesi with book as one of the forms of learning media. This application is designed by using and implement Augmented Reality technology with Marker-Based method.